Melatonin ameliorates age-related sarcopenia by inhibiting fibrogenic conversion of satellite cell - Guo-Zheng Zhu; Kai Zhao; Hong-Zhou Li; Di-Zheng Wu; Yun-Biao Chen; Dong Han; Jia-Wen Gao; Xing-Yu Chen; Yong-Peng Yu; Zhi-Wei Huang; Chen Tu; Zhao-Ming Zhong (BMC, 2024)
Abstract The fibrogenic conversion of satellite cells contributes to the atrophy and fibrosis of skeletal muscle, playing a significant role in the pathogenesis of age-related sarcopenia. Melatonin, a hormone secreted by the pineal gland, exhibits anti-aging and anti-fibrotic effects in various conditions. However, the effect of melatonin on satellite cell fate and age-related sarcopenia remains under-explored. Here, we report that melatonin treatment mitigated the loss of muscle mass and strength in aged mice, replenished the satellite cell pool and curtailed muscle fibrosis. When primary SCs were cultured in vitro and subjected to aging induction via d-galactose, they exhibited a diminished myogenic potential and a conversion from myogenic to fibrogenic lineage. Notably, melatonin treatment effectively restored the myogenic potential and inhibited this lineage conversion. Furthermore, melatonin attenuated the expression of the fibrogenic cytokine, transforming growth factor-β1, and reduced the phosphorylation of its downstream targets Smad2/3 both in vivo and in vitro. In summary, our findings show melatonin's capacity to counteract muscle decline and inhibit fibrogenic conversion in aging SCs and highlight its potential therapeutic value for age-related sarcopenia. Graphical Abstract